ANALISIS BIAYA PENGGUNAAN ALAT BERAT PADA PEKERJAAN PEMBANGUNAN LAPANGAN SEPAK BOLA KOMPLEKS TAKAWA KEC.PASARWAJO - Sianto, La (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
In project work, heavy equipment is needed in the implementation of the work. In project work, most of the work uses heavy equipment, it is necessary to first analyze the needs of the equipment according to the time and cost and work items in the field before renting the equipment used. The heavy equipment that will be used for this research is heavy equipment for soccer field work in the Takawa complex, Pasarwajo District, Buton Regency. This research was carried out in order to be able to analyze the need for heavy equipment usage and be able to calculate equipment rental costs. In the existing heavy equipment used are Excavator, Dump Truck, Motor Grader, Vibro Roller. Working time depends on the workload of the equipment used, while the calculated implementation costs are rental costs, mobilization and demobilization costs, and operating costs such as fuel and operators. The results of the binamarga analysis calculation, the heavy equipment needed is one Unit Excavator, three Dump Trucks, one Motor Grader Unit, one Vibro Roller Unit, with the total rental cost of the heavy equipment is Rp. 583,297,377 with the time given is 52 days. And the results of direct analysis in the field calculate the heavy equipment needed, namely 2.2 Excavator Units, 3 Dump Trucks, 1 Motor Grader Unit, 1 Vibro Roller Unit. with the total rental cost of the heavy equipment is Rp. 562,082,800 with a given time of 52 days. Keywords: Cost, Productivity, RAB, Heavy Equipment and Highways